Complete genome of the switchgrass endophyte Enterobacter clocace P101. Issue 3 (November 2014) - Humann, Jodi; Wildung, Mark; Pouchnik, Derek; Bates, Austin; Drew, Jennifer; Zipperer, Ursula; Triplett, Eric; Main, Dorrie; Schroeder, Brenda
Abstract TheEnterobacter cloacae complex is genetically very diverse. The increasing number of complete genomic sequences ofE. cloacae is helping to determine the exact relationship among members of the complex.E. cloacae P101 is an endophyte of switchgrass (Panicum virgatum ) and is closely related to otherE. cloacae strains isolated from plants. The P101 genome consists of a 5, 369, 929 bp chromosome. The chromosome has 5, 164 protein-coding regions, 100 tRNA sequences, and 8 rRNA operons.